The A.K. Party and the Kurds since 2014: a discourse of terror. Issue 4 (8th August 2018) - Martin, Natalie
Abstract: This article will examine A.K.P. (Adalet ve Kalkınma Partisi) discourse surrounding 'terrorism' and political violence in Turkey since 2014, concentrating on issues pertaining to the Kurdish question. It explores whether the Turkish government has used its state powers for countering political violence to neuter political opposition in various forms. It analyses the public discourse of the A.K.P. elite to argue that the Turkish government has redefined 'terrorist' to mean 'opponent'. This highlights a discursive strategy of associating perceived threats—the P.Y.D. (Partiya Yekitiya Demokrat), the H.D.P. (Halklarin Demokratik Partisi), Academics for Peace and Amnesty International—with terrorist actors: the P.K.K. (Partiya Karkerên Kurdistan) and Islamic State (I.S.). Taking a critical theoretical approach using securitization theory it explores the underlying power structures at play within this scenario to argue additionally that having initially de-securitized the role of I.S. in Turkey the A.K.P. has, since 2015, re-securitized I.S. for its own purposes including the ongoing delegitimization of its opponents. Ultimately, the widening and apparent malleability of the 'terrorist' label in Turkey should be seen as both a symptom of the country's authoritarian drift since 2007 and a means of sustaining it further.